Conductometric Studies of Aqueous Solution of Thymine and Adenosine At Different Temperatures - Al-Ani, S. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Molar conductivity of different concentrations of thymine and adenosine in water , sodium acetate and ammonium chloride solution at different temperatures , 283. 15-323.15  K has been determined from direct conductivity measurements , examination of aqueous mixture of thymine and adenosine with Onsager equation reveal deviation from linearity at high concentration .This deviation was explained in term of molecular interaction . Ostwald dilution law also examined with the above mixtures lead to calculation of limiting molar conductivities and dissociation constants of both  nucleic acid in water , sodium acetate and ammonium chloride. The agreement between the values obtained for Onsager equation and Ostwald law was reasonable . Calculation of activation energies of flow using modified Arrhenius equation gives a result showed that the molecular interaction of both acids in all different mixtures were the same .